Assessment of contamination of natural waters with radionuclides and heavy metals the case of Karabulak creek at the Semipalatinsk Test Site. - Madina Dyussembayeva; Almira Aidarkhanova; Azhar Tashekova; Yerbol Shakenov; Vladimir Kolbin; Alyona Merkel; Fail Zhamaldinov; Natalya Larionova; Igor Gorlachev; Pavel Kharkin; Sergey Lukashenko; Yelena Yevlampiyeva (PLoS ONE)
This paper presents research data on water contamination levels of artificial radionuclides and heavy metals in Karabulak Creek at the Semipalatinsk Test Site. The uranium isotopic composition has been studied (235U and 238U). Priority contaminants and the most 'contaminated' sections of the Karabulak creek were identified, and water quality-related indicators were also estimated. The environmental situation around Karabulak Creek at the «Degelen» site-at which underground nuclear tests have been conducted-was found to be unique and attributed to the combined effect of man-made radiation and natural factors and, in particular, to geochemical features of the region.